Urban youth subjective well-being in Malaysia: potential factors - Ramli, Siti Aisyah; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Idris, Khairuddin; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
This conceptual paper aims to identify the potential factors for subjective well-being among urban youth in Malaysia. To understand urban youth’s subjective well-being is important as it offers a comprehensive view on the issue. Based on a review of literature and document analyses, it concludes that subjective well-being is not merely covering the tangible aspects such as physical infrastructure and the economy, but also the non-tangible aspects such as emotional, social, political, spiritual, psychological, happiness and others.